Closing the gap: Gender and innovation - Laura Barasa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Innovation generally takes place in male-dominated industries. A gender gap might therefore exist. This study used data from the 2015 Tanzania Firm-Level Skills Survey to investigate the gender innovation gap between female-owned enterprises and male-owned enterprises. A non-linear Blinder-Oaxaca decomposition was used to decompose the mean differences in innovation performance into the endowments effect that reflects resource endowments and the coefficients effect relating to resource utilization. The study found that female-owned enterprises faced an 18.1 percentage point lower probability of innovation when compared to male-owned enterprises. The endowments effect had a positive association with the gender innovation gap. In contrast, the coefficients effect was negatively associated with the gender innovation gap. Policies aimed at reducing gender inequalities in innovation need to strike a balance between enhancing resource acquisition by female-owned enterprises and improving resource utilization by their male counterparts to prevent reversals in the gender innovation gap.
Keywords: J16; O30; O31; 330; female-owned enterprises; non-linear Blinder-Oaxaca decomposition; gender gap; innovation; Tanzania